The factors of food intake pattern towards the health preference among UMK student - Ee, Gim Aei; Ausaini, Muhammad Faisal Husseini; Boiman, Nurul Amirah Afiqah; Yahaya, Yoheskail (2015)
Everyday food choices will affect the health condition on how the consumers feel now, tomorrow and in future. This study aims to determine the health preference and pattern of food intake among UMK students. A total number of 346 students aged between 18-26 years old were randomly selected to complete a close-end questionnaire. The questionnaire were include question on demographic information, factor that influence food intake and the relationship between the factor and food intake pattern. The factors determined were knowledge, price, availability and budget. There were 41.6% male participant and 58.4% female participants participate in this study. There were 34.1% students age 18-20 years old, 62.1% student age 21-23 years old and 3.8% student aged 24-26 years old. Majority of the participants were Malay (63%), followed by Chinese (19.4%), Indian (9.5%) and others (8.1). Result shown that the main factor that influence that healthy food intake pattern among UMK students were budget (P=0.0001), followed by pricing (P=0.0005), then knowledge (P=0.0017) and availability (P=0.453). In conclusion, the food intake patterns by UMK students were influence mainly by budget and price of the foods.